Prevalence of intestinal parasitic contamination in fresh vegetables in Bangkok, Thailand, and surrounding areas: A cross-sectional survey - Pokkamol Laoraksawong; Uthaitip Bunkasem; Anunya Pradidthaprecha (Parasite Epidemiology and Control)
Intestinal parasitic infections are a major public health issue worldwide, and vegetables contaminated with these parasites have been implicated in their transmission. This study investigated the prevalence and distribution of intestinal parasites (IPs) on fresh vegetables in Bangkok, Thailand, and surrounding areas. This cross-sectional survey was conducted from November 1 to December 31, 2022. Vegetable samples were purchased from 12 markets in Bangkok and on surrounding areas. A total of 1800 fresh vegetable samples were collected and examined using direct wet-mount microscopy by parasitologists. The total prevalence of IPs in fresh vegetables was 21.17 %, with the highest prevalence observed in peppermint (79.17 %), followed by Thai basil (72.50 %) and Centella asiatica (40.83 %). Soil-transmitted helminths were predominantly detected, including hookworm larvae (13.06 %), Strongyloides spp. (rhabditiform larvae) (6.61 %), and Ascaris lumbricoides (2.50 %). Furthermore, open-air markets in rural areas had a 1.40 times higher chance (95 % CI: 1.10–1.74, P = 0.005) of IP contamination in vegetables than structured markets in urban areas. Additionally, fresh products in rural open-air markets were 8.54 times more likely to be contaminated with Blastocystis sp. (95 % CI: 2.57–28.40, P < 0.001) and 2.46 times more likely to be contaminated with Taeniidae spp. (95 % CI: 1.01–5.95, P = 0.036) compared to produce from structured markets in urban areas. The presence of these parasites in fresh vegetables highlights the need for improved food safety measures, including proper hygiene practices during vegetable cultivation, harvesting, transportation, and storage. Public health education campaigns on the risks of consuming contaminated vegetables should also be implemented to reduce the burden of intestinal parasitic infections in Thailand.